High-permeability-selectivity cellulose-based nanofiltration membrane as well as preparation method and application thereof

By forming a charged amino acid intermediate layer on the surface of the ultrafiltration membrane of the nanofiltration membrane and forming a cellulose-based polyamide layer, the problem of poor selectivity of the existing nanofiltration membrane when improving permeability is solved, and the preparation of a high-permeability-selective cellulose-based nanofiltration membrane is realized, which is suitable for drinking water treatment and brine separation.

CN119499886AActive Publication Date: 2025-02-25NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202510096024.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-02-25
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

The existing nanofiltration membranes have poor selectivity when improving permeability, and cannot significantly improve permeability without reducing selectivity, resulting in limited applications in the fields of water treatment and brine separation.

Method used

A highly permeable-selective cellulose-based nanofiltration membrane was prepared by forming a charged amino acid intermediate layer on the surface of the ultrafiltration membrane and forming a cellulose-based polyamide layer on the surface of the intermediate layer through interfacial polymerization. This method utilizes the reaction-diffusion mechanism and the dual constraint mechanism to significantly improve the permeability and selectivity of the membrane.

Benefits of technology

It has achieved significant improvement in the permeability of the nanofiltration membrane without reducing selectivity, the pure water flux reaches 18 LMH bar-1 or above, and the retention rate of various salts reaches 95% or above. It is suitable for drinking water treatment and brine separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499886A_ABST
    Figure CN119499886A_ABST
Patent Text Reader

Abstract

The invention discloses a high-permeability-selectivity cellulose-based nanofiltration membrane as well as a preparation method and application thereof. The preparation method comprises the following steps: providing an ultrafiltration membrane as a substrate layer; placing the ultrafiltration membrane in a middle layer liquid containing charged amino acid for dipping treatment so as to form a charged amino acid middle layer on the surface of the ultrafiltration membrane; and forming a cellulose-based polyamide layer on the surface of the middle layer by adopting an interfacial polymerization reaction so as to prepare the high-permeability-selectivity cellulose-based nanofiltration membrane, wherein a water phase solution adopted in the interfacial polymerization reaction comprises cellulose substances and diamine, and an organic phase solution comprises polyacyl chloride. The high-permeability-selectivity cellulose-based nanofiltration membrane disclosed by the invention has excellent pure water permeability and salt rejection rate, and can be widely applied to the fields of drinking water treatment, saline water separation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanofiltration membranes, and in particular relates to a high permeability-selectivity cellulose-based nanofiltration membrane and a preparation method and application thereof. Background Art

[0002] The water resources on the earth are very limited, with ocean water accounting for 97.4% of the total and fresh water only 2.6%. Due to human factors or changes in the natural environment, global resource and environmental problems are becoming increasingly severe, and environmental problems mainly related to freshwater resources have become one of the difficulties that people need to solve. The water that the human body needs to consume requires certain minerals and trace elements, so there is very little water available for us humans to drink directly, so solving the drinking water purification crisis is urgent.

[0003] At present, there are many technologies for processing seawater resources to produce water that can be directly drunk by humans. In recent years, membrane separation technology has become a key technology in water treatment technology. Nanofiltration (NF) membrane is a pressure-driven membrane developed based on reverse osmosis separation technology. Nanofiltration can remove macromolecules with a molecular weight greater than 200Da because of its screening pore size of about 1nm and a molecular weight cutoff of 200-1000Da, and the interception rate is above 90%. The operating range of nanofiltration membrane is between ultrafiltration and reverse osmosis. It intercepts organic matter with a molecular weight of about 150~500, and its ability to intercept soluble salts is between 20%~98%. The corresponding pore size is ≤2 nm, which has a good pore size screening effect, and the desalination of monovalent anion salt solution is lower than that of high-valent anion solution. Therefore, nanofiltration technology is widely used in wastewater treatment, water softening, food processing, pharmaceutical industry, etc. Existing nanofiltration membranes are usually polyamide nanofiltration membranes, which are often prepared by interfacial polymerization. Two highly reactive monomers (water-phase amine monomers and oil-phase acyl chloride monomers) are dissolved in two immiscible solvents respectively, and irreversible polycondensation reactions are carried out at the interface of the two liquid phases to form a densely structured polyamide nanofiltration membrane. The commonly used water-phase monomers are piperazine (PIP) and the oil-phase monomers are 1,3,5-benzenetricarboxylic acid chloride (TMC). Nanofiltration membranes are usually separated and selected by the combined action of multiple separation principles such as the Donan effect, dielectric effect, and size screening effect. However, nanofiltration membranes have the disadvantage of membrane separation, the "trade-off effect" of permeability-selectivity, that is, when the permeability is good, the selectivity is poor, and when the selectivity is high, the permeability is very low. Therefore, it is worth studying to prepare a nanofiltration membrane that breaks the "trade-off effect" and improves permeability without reducing selectivity.

[0004] In order to effectively break the "trade-off effect", researchers have conducted many different studies, including modification of the base membrane, such as sulfonation of the base membrane to make it hydrophilic, and the addition of water phase additives, such as MOFs, COFs, surfactants, inorganic nanoparticles such as SiO2, carbon quantum dots, graphene, carbon nanotubes, etc. However, these additives cannot guarantee the improvement of permeability without reducing selectivity, and inorganic nanoparticles have problems such as easy agglomeration and difficulty in dispersion, resulting in uneven membranes. Summary of the invention

[0005] The main purpose of the present invention is to provide a high permeability-selectivity cellulose-based nanofiltration membrane and its preparation method and application, so as to overcome the shortcomings of the prior art.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: The embodiment of the present invention provides a method for preparing a highly permeable-selective cellulose-based nanofiltration membrane, which comprises: providing an ultrafiltration membrane as a substrate layer; The ultrafiltration membrane is immersed in an intermediate layer liquid containing charged amino acids, thereby forming an intermediate layer of charged amino acids on the surface of the ultrafiltration membrane; And, an interfacial polymerization reaction is used to form a cellulose-based polyamide layer on the surface of the intermediate layer, thereby preparing a high permeability-selective cellulose-based nanofiltration membrane; wherein the aqueous phase solution used in the interfacial polymerization reaction includes a cellulose-like substance and a diamine, and the organic phase solution includes a polyacid chloride.

[0007] An embodiment of the present invention also provides a high permeability-selective cellulose-based nanofiltration membrane obtained by the aforementioned preparation method, wherein the high permeability-selective cellulose-based nanofiltration membrane comprises a base layer, a charged amino acid intermediate layer and a cellulose-based polyamide layer stacked in sequence; wherein the cellulose-based polyamide layer has a wrinkled Turing structure.

[0008] The embodiments of the present invention also provide the use of the aforementioned high permeability-selectivity cellulose-based nanofiltration membrane in the field of drinking water treatment or salt water separation.

[0009] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention utilizes the reaction-diffusion mechanism to prepare a highly permeable-selective cellulose-based nanofiltration membrane under the dual constraints of the interaction between charged amino acids and cellulose and diamines; (2) The amino acids in the present invention are biological macromolecules with obvious zwitterionic characteristics and controllable charges. Due to the different groups they carry, their charges in water are different; (3) The cellulose in the present invention is easily available and inexpensive, making the method for preparing cellulose-based nanofiltration membranes easier to industrialize; (4) The pure water flux of the highly permeable-selective cellulose-based nanofiltration membrane of the present invention reaches 18 LMH bar -1 And above, the interception rate of various salts reaches 95% and above, especially high-priced salts, which can be widely used in drinking water treatment, making it easier for people to obtain directly drinkable water resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0011] Figure 1 is an infrared characterization image of the nanofiltration membrane in Examples 1, 2, 4 and 6 of the present invention; Figure 2a-2d is a SEM image of the nanofiltration membrane in Examples 1, 2, 4 and 6 of the present invention; Figure 3 is a graph of the separation performance of the nanofiltration membranes in Examples 1, 2, 4 and 6 of the present invention. DETAILED DESCRIPTION

[0012] In view of the defects of the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. It mainly utilizes the wrinkled Turing polyamide nanofiltration membrane formation mechanism - reaction-diffusion, and jointly prepares a highly permeable and selective cellulose-based nanofiltration membrane with charged amino acids as the middle layer under double inhibition.

[0013] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0014] Specifically, as one aspect of the technical solution of the present invention, a method for preparing a highly permeable-selective cellulose-based nanofiltration membrane includes: providing an ultrafiltration membrane as a substrate layer; The ultrafiltration membrane is immersed in an intermediate layer liquid containing charged amino acids, thereby forming an intermediate layer of charged amino acids on the surface of the ultrafiltration membrane; And, an interfacial polymerization reaction is used to form a cellulose-based polyamide layer on the surface of the intermediate layer, thereby preparing a high permeability-selective cellulose-based nanofiltration membrane; wherein the aqueous phase solution used in the interfacial polymerization reaction includes a cellulose-like substance and a diamine, and the organic phase solution includes a polyacid chloride.

[0015] In some preferred embodiments, the ultrafiltration membrane includes any one or more combinations of polyethersulfone membrane, polyvinyl chloride membrane, triacetyl cellulose membrane, polyvinylidene fluoride ultrafiltration membrane, and is not limited thereto.

[0016] In some preferred embodiments, the charged amino acids include any one or more combinations of glycine, glutamic acid, aspartic acid, arginine, and lysine, but are not limited thereto.

[0017] In some preferred embodiments, the cellulose-based material is cellulose and its derivatives containing hydrophilic active groups, and the cellulose-based material includes any one or more combinations of ethyl cellulose, carboxymethyl cellulose, cellulose nanocrystals, and cellulose powder, but is not limited thereto.

[0018] Furthermore, the cellulose nanocrystals, cellulose powder, etc. all contain hydrophilic active groups.

[0019] In some preferred embodiments, the diamine includes any one or more combinations of ethylenediamine, hexamethylenediamine, piperazine, m-phenylenediamine, p-phenylenediamine, and polyethyleneimine, but is not limited thereto.

[0020] In some preferred embodiments, the polyacid chloride includes any one or more combinations of trimesoyl chloride, 3,4′,5-biphenyltrichloride, 3,3′,5,5′-biphenyltetrachloride, isophthaloyl chloride, 5-isocyanate isophthaloyl chloride, and 5-oxocarbonyl isophthaloyl chloride, and is not limited thereto.

[0021] In some preferred embodiments, the preparation method specifically comprises: Pre-treating the ultrafiltration membrane; Mixing charged amino acids with water to form an intermediate layer liquid; Also, the ultrafiltration membrane obtained by the pretreatment is immersed in the intermediate layer liquid for 8 to 10 minutes, and then the excess solution is taken out and removed, thereby forming a charged amino acid intermediate layer on the surface of the ultrafiltration membrane.

[0022] Furthermore, the mass ratio of the charged amino acid to water in the intermediate layer liquid is 0.01-0.03:100.

[0023] In some preferred embodiments, the preparation method specifically comprises: Mixing the cellulose material, the diamine and water to form an aqueous solution; mixing a polyacid chloride with an organic phase solvent to form an organic phase solution; Furthermore, the obtained ultrafiltration membrane is placed in an aqueous solution and an organic solution in sequence for interfacial polymerization reaction, and then solidified to obtain a high permeability-selectivity cellulose-based nanofiltration membrane.

[0024] Furthermore, the concentration of the diamine in the aqueous solution is 0.20-0.40 wt %.

[0025] Furthermore, the concentration of the cellulose substance in the aqueous solution is 0.005-0.010 wt %.

[0026] Furthermore, the concentration of the polyacid chloride in the organic phase solution is 0.10-0.30 wt %.

[0027] Furthermore, the mass ratio of the cellulose material to the diamine is 0.005-0.010:0.20-0.40.

[0028] Furthermore, the curing treatment is carried out at a temperature of 60-80°C and a time of 8-10 min.

[0029] In some preferred embodiments, the method for preparing the highly permeable-selective cellulose-based nanofiltration membrane comprises the following steps: (1) Ultrafiltration membrane pretreatment: Soak the polyethersulfone ultrafiltration membrane in 75% anhydrous ethanol at room temperature, and then wash it with deionized water; (2) Mix different charged amino acids in a certain ratio to obtain an intermediate layer liquid; the optimal condition is that the ratio of charged amino acids to water in the intermediate layer liquid is 0.01-0.03wt%; (3) Mixing cellulose and its derivatives with hydrophilic active groups with a quantitative diamine solution in a certain ratio to obtain an aqueous phase liquid; the optimal conditions are: the mass fraction ratio of cellulose and its derivatives: diamine monomer is 0.005~0.010:0.20~0.40; (4) mixing the polyacyl chloride and the organic phase solvent and stirring until they are completely dissolved to prepare an organic phase solution; (5) Using the interfacial polymerization method, the pretreated ultrafiltration membrane is immersed in the intermediate layer liquid for a period of time. After removing the excess solution, it is immersed in the aqueous phase solution, the excess aqueous phase solution on the surface is removed, and it is placed in the organic phase solution for reaction. Finally, the reacted membrane is placed in a vacuum drying oven for curing treatment to obtain a cellulose nanofiltration membrane with charged amino acids as the intermediate layer.

[0030] In the present application, the charged amino acid intermediate layer and the cellulose-based polyamide layer are deposited on one side of the ultrafiltration membrane.

[0031] Another aspect of an embodiment of the present invention also provides a high permeability-selective cellulose-based nanofiltration membrane prepared by the aforementioned preparation method, wherein the high permeability-selective cellulose-based nanofiltration membrane comprises a base layer, a charged amino acid intermediate layer and a cellulose-based polyamide layer stacked in sequence; wherein the cellulose-based polyamide layer has a wrinkled Turing structure.

[0032] Furthermore, the thickness of the cellulose-based polyamide layer is 100 nanometers.

[0033] Turing structure nanofiltration membranes are usually formed by interfacial polymerization to form uniform nodules or stripes. Only nodular structures are observed in existing commercial membranes. Polyamide nanofiltration membranes are prepared based on interfacial polymerization. The preparation of wrinkled polyamide nanofiltration membranes usually utilizes a reaction-diffusion mechanism, which is a competition between two factors, one called an "activator" and the other called an "inhibitor" to inhibit the autocatalytic properties of the activator. The key is that the two factors must have a large diffusion rate difference to have a large difference in morphology, that is, by adding substances that have a certain interaction (hydrogen bonding and electrostatic interaction) with the aqueous phase diamine monomer, the diffusion rate of the aqueous phase is inhibited, forming a certain diffusion rate difference.

[0034] The method provided by the present invention is characterized in that green and safe cellulose and its derivatives and biomacromolecule amino acids are selected as preparation raw materials, different charged amino acids have different charges in the aqueous phase solution (alkaline), and the amino acids with different charges have different hydrogen bonds and electrostatic interactions with diamines, which inhibit the diffusion of the aqueous phase to the oil phase and fix the diamine monomers on the substrate. In addition, because the cellulose with hydrophilic active groups is added to the aqueous phase of interfacial polymerization, the hydrophilic groups and the diamines in the aqueous phase form hydrogen bonds and electrostatic interactions, which can increase the viscosity of the aqueous phase and reduce the diffusion rate of the aqueous phase to the oil phase. Under the dual constraints, the diffusion rate of the aqueous phase diamines is significantly reduced, so that a wrinkled polyamide layer is formed. The effect of hydrogen bonds and the aqueous phase solution with dispersed balance make the prepared polyamide nanofiltration membrane have a wrinkled polyamide layer, and both the pure water permeability and the salt retention rate are greatly improved. Under the dual constraints of amino acids and cellulose on diamine monomers, the present invention jointly prepares a high permeability-selective cellulose-based nanofiltration membrane with charged amino acids as the intermediate layer, which can be widely used in drinking water treatment, salt water separation and other fields.

[0035] In some preferred embodiments, the pure water flux of the highly permeable-selective cellulose-based nanofiltration membrane is 15LMH bar. -1 above.

[0036] In some preferred embodiments, the high permeability-selective cellulose-based nanofiltration membrane has a salt rejection rate of more than 90%.

[0037] Another aspect of the embodiments of the present invention further provides use of the aforementioned high permeability-selectivity cellulose-based nanofiltration membrane in the field of drinking water treatment or salt water separation.

[0038] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0039] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.

[0040] Example 1 The present invention provides a method for preparing a highly permeable and selective cellulose-based nanofiltration membrane with a charged amino acid as an intermediate layer, comprising the following steps: Step 1: Pretreatment of the ultrafiltration membrane: Soak the polyethersulfone ultrafiltration membrane in 75% anhydrous ethanol at room temperature, and then wash it with deionized water; Step 2, adding positively charged lysine at a mass fraction of 0.10% to obtain an intermediate layer liquid; Step 3: Mix cellulose nanocrystals and anhydrous piperazine at a mass fraction ratio of 0.005:0.35 and stir until completely dissolved to prepare an aqueous solution.

[0041] Step 4: Mix trimesoyl chloride in n-hexane solvent at a mass fraction of 0.25%, and stir until completely dissolved to prepare an organic phase solution; Step 5: Using the interfacial polymerization method, the pre-treated ultrafiltration membrane is placed in the intermediate layer liquid for a period of time, the excess surface solution is removed, and then immersed in the aqueous phase solution for a period of time, the excess surface aqueous phase solution is removed, and the membrane is placed in the organic phase solution for reaction. Finally, the membrane after the reaction is placed in a 60°C vacuum drying oven for curing treatment to obtain a cellulose-based nanofiltration membrane with amino acids as the intermediate layer; the infrared characterization of the nanofiltration membrane is shown in FIG. Figure 1 As shown in the SEM images Figure 2a As shown, the separation performance is Figure 3 When tested with a magnesium sulfate solution with a concentration of 2000ppm at a pressure of 0.4MPa, the water flux of the membrane was 19.6LMHbar -1 , the retention rate of magnesium sulfate is 96.4%.

[0042] Example 2 Step 1: Ultrafiltration membrane pretreatment: Soak the polyvinylidene fluoride ultrafiltration membrane in 75% anhydrous ethanol at room temperature, and then wash it with deionized water; Step 2, adding positively charged lysine at a mass fraction of 0.10% to obtain an intermediate layer liquid; Step 3: Mix cellulose nanocrystals and anhydrous piperazine at a mass fraction ratio of 0.005:0.35 and stir until completely dissolved to prepare an aqueous solution.

[0043] Step 4: Mix trimesoyl chloride in n-hexane solvent at a mass fraction of 0.25%, and stir until completely dissolved to prepare an organic phase solution; Step 5: Using the interfacial polymerization method, the pre-treated ultrafiltration membrane is placed in the intermediate layer liquid for a period of time, the excess surface solution is removed, and then immersed in the aqueous phase solution for a period of time, the excess surface aqueous phase solution is removed, and the membrane is placed in the organic phase solution for reaction. Finally, the membrane after the reaction is placed in a 60°C vacuum drying oven for curing treatment to obtain a cellulose-based nanofiltration membrane with amino acids as the intermediate layer; the infrared characterization of the nanofiltration membrane is shown in FIG. Figure 1 As shown in the SEM images Figure 2b As shown, the separation performance is Figure 3 When tested with a magnesium sulfate solution with a concentration of 2000ppm at a pressure of 0.4MPa, the water flux of the membrane was 15.8LMHbar -1 , the retention rate of magnesium sulfate is 91.3%.

[0044] Example 3 Steps 1, 3, 4 and 5 are the same as those in Example 1, except that in step 2, negatively charged lysine is replaced with negatively charged glutamic acid to obtain a cellulose-based nanofiltration membrane with amino acids as the middle layer; the membrane was tested with a magnesium sulfate solution with a concentration of 2000 ppm at a pressure of 0.4 MPa, and the water flux of the membrane was 13.2 LMHbar -1 , the retention rate of magnesium sulfate is 92.2%.

[0045] Example 4 Steps 1, 2, 4 and 5 are the same as those in Example 1, except that the mass fraction ratio of cellulose nanocrystals to anhydrous piperazine in step 3 is changed to 0.010:0.30, and a cellulose-based nanofiltration membrane with amino acids as the middle layer is obtained; the infrared characterization image of the nanofiltration membrane is as shown in Figure 1 As shown in the SEM images Figure 2c As shown, the separation performance is Figure 3 When tested with a magnesium sulfate solution with a concentration of 2000ppm at a pressure of 0.4MPa, the water flux of the membrane was 16.5 LMHbar -1 , the retention rate of magnesium sulfate is 92.4%.

[0046] Example 5 Steps 1, 2, 4 and 5 are the same as those in Example 1, except that in step 3, the mass fraction ratio of cellulose nanocrystals to anhydrous piperazine is changed to 0.008:0.40, and a cellulose-based nanofiltration membrane with an amino acid as an intermediate layer is obtained; the membrane is tested with a magnesium sulfate solution with a concentration of 2000 ppm at a pressure of 0.4 MPa, and the water flux of the membrane is 17.3 LMHbar -1 , the retention rate of magnesium sulfate is 95.1%.

[0047] Example 6 Steps 1, 2, 3 and 5 are the same as those in Example 1, except that in step 4, the mass fraction of trimesoyl chloride in n-hexane solvent is changed to 0.20%, thereby obtaining a cellulose-based nanofiltration membrane with amino acids as the intermediate layer; the infrared characterization image of the nanofiltration membrane is shown in FIG. Figure 1 As shown in the SEM images Figure 2d As shown, the separation performance is Figure 3 When tested with a magnesium sulfate solution with a concentration of 2000ppm at a pressure of 0.4MPa, the water flux of the membrane was 15.6 LMHbar -1 , the retention rate of magnesium sulfate is 92.6%.

[0048] Example 7 Steps 1, 2, 3 and 4 are the same as those in Example 1, except that the heat treatment temperature in step 5 is changed to 80°C, and a cellulose-based nanofiltration membrane with an amino acid as the intermediate layer is obtained; the membrane is tested with a magnesium sulfate solution with a concentration of 2000 ppm at a pressure of 0.4 MPa, and the water flux of the membrane is 15.2 LMHbar -1 , the retention rate of magnesium sulfate is 94.2%.

[0049] Comparative Example 1 The method is the same as in Example 1, except that: the intermediate layer liquid is missing; the cellulose-based nanofiltration membrane is tested with a magnesium sulfate solution with a concentration of 2000 ppm under a pressure of 0.4 MPa, and the water flux of the membrane is 14.9 LMHbar -1 , where the retention rate of magnesium sulfate is 91.0%.

[0050] Comparative Example 2 The method is the same as Example 1, except that step 2 is omitted and positively charged lysine is placed in an aqueous solution. The composite nanofiltration membrane is tested with a magnesium sulfate solution with a concentration of 2000 ppm at a pressure of 0.4 MPa. The water flux of the membrane is 13.2 LMHbar -1 , the retention rate of magnesium sulfate is 90.4%.

[0051] Comparative Example 3 The method is the same as in Example 1, except that the aqueous solution lacks cellulose nanocrystals. The nanofiltration membrane obtained was tested with a magnesium sulfate solution with a concentration of 2000 ppm at a pressure of 0.4 MPa, and the water flux of the membrane was 9.8 LMHbar -1 , the retention rate of magnesium sulfate is 89.9%.

[0052] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0053] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a highly permeable-selective cellulose-based nanofiltration membrane, characterized in that: include: providing an ultrafiltration membrane as a substrate layer; The ultrafiltration membrane is immersed in an intermediate layer liquid containing charged amino acids, thereby forming an intermediate layer of charged amino acids on the surface of the ultrafiltration membrane; And, an interfacial polymerization reaction is used to form a cellulose-based polyamide layer on the surface of the intermediate layer, thereby preparing a high permeability-selective cellulose-based nanofiltration membrane; wherein the aqueous phase solution used in the interfacial polymerization reaction includes a cellulose-like substance and a diamine, and the organic phase solution includes a polyacid chloride.

2. The preparation method according to claim 1, characterized in that: The ultrafiltration membrane includes any one or more combinations of polyethersulfone membrane, polyvinyl chloride membrane, triacetylcellulose membrane, and polyvinylidene fluoride ultrafiltration membrane; And / or, the charged amino acids include any one or more combinations of glycine, glutamic acid, aspartic acid, arginine, and lysine; And / or, the cellulose material is cellulose containing hydrophilic active groups and its derivatives, and the cellulose material includes any one or more combinations of ethyl cellulose, carboxymethyl cellulose, cellulose nanocrystals, and cellulose powder; And / or, the diamine includes any one or more combinations of ethylenediamine, hexamethylenediamine, piperazine, m-phenylenediamine, p-phenylenediamine, and polyethyleneimine; And / or, the polyacid chloride includes any one or more combinations of trimesoyl chloride, 3,4′,5-biphenyltrichloride, 3,3′,5,5′-biphenyltetrachloride, isophthaloyl chloride, 5-isocyanate isophthaloyl chloride, and 5-oxocarbonyl isophthaloyl chloride.

3. The preparation method according to claim 1, characterized in that: Specifically include: Pre-treating the ultrafiltration membrane; Mixing charged amino acids with water to form an intermediate layer liquid; Also, the ultrafiltration membrane obtained by the pretreatment is immersed in the intermediate layer liquid for 8 to 10 minutes, and then the excess solution is taken out and removed, thereby forming a charged amino acid intermediate layer on the surface of the ultrafiltration membrane.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the charged amino acid to water in the intermediate layer liquid is 0.01-0.03:

100.

5. The preparation method according to claim 1, characterized in that: Specifically include: Mixing the cellulose material, the diamine and water to form an aqueous solution; mixing a polyacid chloride with an organic phase solvent to form an organic phase solution; Furthermore, the obtained ultrafiltration membrane is placed in an aqueous solution and an organic solution in sequence for interfacial polymerization reaction, and then solidified to obtain a high permeability-selectivity cellulose-based nanofiltration membrane.

6. The preparation method according to claim 5, characterized in that: The concentration of the diamine in the aqueous phase solution is 0.20-0.40 wt %; and / or, the concentration of the cellulose substance in the aqueous solution is 0.005-0.010 wt %; and / or, the concentration of the polyacid chloride in the organic phase solution is 0.10-0.30wt%; And / or, the mass ratio of the cellulose material to the diamine is 0.005-0.010:0.20-0.

40.

7. The preparation method according to claim 5, characterized in that: The curing process is performed at a temperature of 60 to 80° C. and for a time of 8 to 10 minutes.

8. A highly permeable-selective cellulose-based nanofiltration membrane prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The high permeability-selectivity cellulose-based nanofiltration membrane comprises a base layer, a charged amino acid middle layer and a cellulose-based polyamide layer which are stacked in sequence; wherein the cellulose-based polyamide layer has a wrinkled Turing structure.

9. The highly permeable-selective cellulose-based nanofiltration membrane according to claim 8, characterized in that: The pure water flux of the highly permeable-selective cellulose-based nanofiltration membrane is 15 LMH bar. -1 above; And / or, the high permeability-selective cellulose-based nanofiltration membrane has a salt rejection rate of more than 90%.

10. Use of the highly permeable-selective cellulose-based nanofiltration membrane according to claim 8 or 9 in the field of drinking water treatment or salt water separation.

Citation Information

Patent Citations

  • Diazonium method coupling gelatin adsorption material and preparation method thereof

    CN104549177A

  • High-flux high-interception-rate positive charge composite nanofiltration membrane and preparing method of high-flux high-interception-rate positive charge composite nanofiltration membrane

    CN105013333A

  • Polyamide semi-permeable membrane, preparation method and application thereof

    CN108079806A

  • Micromolecule-modified nanofiber-based composite nanofiltration membrane and preparation method thereof

    CN109925892A

  • Anti-fouling and anti-oxidation polyamide composite reverse osmosis membrane and preparation method thereof

    CN110975644A